Introduction to the genomics of infectious diseases. Issue 2 (February 2021) - Rafi, Imran; Hayward, Judith; English, Peter
The COVID-19 Genomics UK (COG-UK) Consortium was created to deliver large-scale and rapid whole-genome virus sequencing. Its data will help Public Health Agencies to manage the COVID-19 pandemic in the UK and inform vaccine research efforts. From a wider perspective, data sharing around the genomics of viruses (and bacteria, protozoa parasites and fungi) offers researchers contrasting perspectives and new biological insights into the evolution of microbes and the development of new tools in managing infectious disease, which on a global scale causes significant mortality. Genomics has an evolving role in pathogen diagnosis and surveillance.